PENGEMBANGAN VIRTUAL LABORATORY BERBASIS MULTIMEDIA INTERAKTIF PADA MATA KULIAH MICROBIOLOGY SUB MATERI ISOLASI BAKTERI - Yeni, Laili Fitri (Jurnal Pendidikan Matematika dan IPA, 2015)
This research aims to produce Virtual Laboratory as interactive multimedia on sub material the isolation of bacteria, knowing about adisability of Virtual Laboratory, and measure the comprehension of the student PGMIPAU Education Biology FKIP Untan concept whom get be taught with Virtual Laboratory. The research method that used is a Development Research. This methodÂ  includes four stages that is the analysis and design stage for produce Virtual Laboratory prototype. The next stage is evaluation and revision until the Virtual Laboratory was proper to use. Implementation of media have done at small group (the student PGMIPAU Education Biology). Be based on result of validation by validator of media and matter, Virtual Laboratory get catagorized as valid with the average of the validation is 3,18. Be based on result of student learnig outcomes obtained average 75,55 with the percentage of completnessÂ  is 88,88%. Keywords: Virtual Laboratory, isolation of bacteria.